THE EFFECT OF THE INTRODUCING METHOD FOR METAL WIRE ON THE PROPERTIES OF THE HALF-MILANO RIB KNITTED FABRIC - LEONOVA, DARYNA; KYZYMCHUK, OLENA (Herald of Khmelnytskyi National University. Technical sciences, 2025)
Protection against electromagnetic radiation is becoming an increasingly important issue not only in industry but also in everyday life due to the increasing number of devices emitted the electromagnetic waves. Although a rigid screen can be used in some cases, a greater flexibility is achieved through the development of bendable, drapeable, and ideally even stretchable screens. Knitted materials are endowed with this ability as well as with potentially good mechanical and thermophysical characteristics, which depend on the structure and the selected raw materials. On the other hand, the necessary physical properties, especially conductivity and magnetic property, have to be added using conductive threads or metal wire. The paper presents the research results on the structure parameters, tensile and thermophysical properties of a hybrid knitted fabric. The hybrid knitted fabrics of Half Milano Rib interlooping were produced from cotton yarn and stainless steel metal wire on a 8 gauge flat bed knitting machine. The obtained results were compared with the corresponding indicators for the knitted fabric of the same interlooping from cotton yarn only. The conducted investigation made it possible to establish the effect of the introducing method for metal wire on the structural parameters and properties of the hybrid knitted fabric. It was found that the Half Milano rib knitted fabric that formed by simultaneously knitting a metal wire with the cotton yarn, has got the highest elasticity and dimensional stability, but the significantly higher thickness and surface density compared to the hybrid knit fabric, in which the courses were formed alternately from the cotton yarn and the metal wire. At the same time, the alternation of courses from cotton yarn and metal wire in the fabric leads to a more significant change in the thermophysical properties of cotton knit fabric, primarily due to the presence of areas with low dencity. Generaly the hybrid knitted fabrics are characterized by a higher degree of heat transfer intensity and better relative vapor permeability compared to the knitted fabric from a cotton yarn only.